Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ ÑÐºÐ²Ð¸Ð»Ð¸Ð±Ñ€Ð°Ñ†Ð¸Ð¸ Ð² ÑÑ€ÐµÐ´Ðµ Ð·Ð°Ð¼Ð¾Ñ€Ð°Ð¶Ð¸Ð²Ð°Ð½Ð¸Ñ Ð½Ð° Ð¾ÑÐ¼Ð¾Ñ‚Ð¸Ñ‡ÐµÑÐºÑƒÑŽ ÑƒÑÑ‚Ð¾Ð¹Ñ‡Ð¸Ð²Ð¾ÑÑ‚ÑŒ Ð¸ Ð¶Ð¸Ð·Ð½ÐµÑÐ¿Ð¾ÑÐ¾Ð±Ð½Ð¾ÑÑ‚ÑŒ 8-ÐºÐ»ÐµÑ‚Ð¾Ñ‡Ð½Ñ‹Ñ… ÑÐ¼Ð±Ñ€Ð¸Ð¾Ð½Ð¾Ð² Ð¼Ñ‹ÑˆÐ¸ - Smolyaninova, E. I.; Khromenkova, O. B.; Zhernoklev, G. V.; Pishko, O. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2004)
Effect of several steps of ultra-rapid freezing in glycerol-sucrose medium on 8-cell mice embryo osmotic resistance and viability has been studied. It has been shown that the procedure of embryos treatment before freezing makes a determinant influence on final embryo survival. The different influence of one-step and two-step addition of the glycerol solutions to embryos on the transport parameters of their plasma membranes has been revealed. The possible mechanisms of detrimental effect of glycerol solutions of high concentrations on membrane structures of mouse embryos are discussed.